Comminuted Scapular Body Fracture after Seizure - Alhamyani, Abdulmohsen Hamad Hamed; Alsayed, Mokhtar Ahmed (International Journal of Innovative Research in Medical Science, 2022)
The current case study deals with Comminuted Scapular Body Fracture after Seizure. Diagnosis of the epilepsy defined as two or more unprovoked seizures. The prevalence of epilepsy is found to be .5 – 2%. People with epilepsy are at risk of fractures either due to fall, muscle contractions that lead for avulsion fractures or loss of protective mechanism during seizures. Muscles contraction during tonic phase of seizures can result in variety of musculoskeletal injuries that include shoulder dislocation or fractures, spine vertebral bodies fractures and acetabular fractures.